The Relationship Between Knowledge Level and Anxiety Level in Facing Menarche A Systematic Review of Cross Sectional Studies - Dwi Mulyati Ningsih; Mizwar Taufiq Firmansyah; Balbina Antonelda M Wawo (Yayasan Adra Karima Hubbi, 2023)
Menarche is the first menstruation in young women. In society, the issue of menstruation is still considered very taboo to discuss, so that young women lack good knowledge and attitudes about physical and psychological changes related to menarche problems. Usually young women will experience anxiety, worry, fear and anxiety when facing menarche. Articles searched via database from 2018-2022. Searches were obtained from the PUBMED and Google Scholar databases. The keywords used are